AN ENGLISH COURSE FOR IMPROVING ENGLISH COMPETENCE OF PRODUCTIVE AGE SOCIETIES - Muh Shofiyuddin (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2016)
In facing globalization and ASEAN Economic Community, English is urgent to be used in working necessity in Indonesia. The writer tries to find the way how to help people meet this urgency. Then the writer holds such effective English course for those who are in 18-25 years old. The course is aimed at: (1) providing English training to the people concerned to meet the demands of employment; (2) helping to improve human resources; (3) driving the spirit of productive age community to work harder; (4) starting English training implementation for free. The course??s learning process uses 30% speaking, 30% writing, 20% listening and 20% reading with 50% English used in teaching. It is assumed that this program is quite effective. They are capable enough to understand and use English after joining the program. This program is very useful to help people in productive age master English in order to get a proper job so as to help the government reduce unemployments.